Professionally oriented Internet environment in the training of future teachers - Drokina, A. S. (Problems of Engineer-Pedagogical Education, 2018)
This article presents the problem of the Internet support in the professional training of future teachers. The analysis of the professionally oriented Internet environment in the training of future specialists has been carried out. In the article pedagogical sites of the Internet are investigated in the sphere of their reference to the system of professional pedagogical education. These sites are aimed to develop such level of future teachers' competence which will help them to integrate opportunities of the Internet into their future professional activity. Such approach to the planning sources of the main kinds of professional information for modern teachers necessary for improvement of the professional activities. The pedagogical tasks are defined which are solved during involvement of future teachers to the active use of the professionally oriented Internet environment to improve their future professional activities.